Improvement in inner retinal function in glaucoma with nicotinamide (vitamin B3) supplementation: A crossover randomized clinical trial. (28th July 2020) - Hui, Flora; Tang, Jessica; Williams, Pete A.; McGuinness, Myra B.; Hadoux, Xavier; Casson, Robert J.; Coote, Michael; Trounce, Ian A.; Martin, Keith R.; van Wijngaarden, Peter; Crowston, Jonathan G.
Abstract: Importance: Retinal ganglion cells endure significant metabolic stress in glaucoma but maintain capacity to recover function. Nicotinamide, a precursor of NAD +, is low in serum of glaucoma patients and its supplementation provides robust protection of retinal ganglion cells in preclinical models. However, the potential of nicotinamide in human glaucoma is unknown. Background: To examine the effects of nicotinamide on inner retinal function in glaucoma, in participants receiving concurrent glaucoma therapy. Design: Crossover, double‐masked, randomized clinical trial. Participants recruited from two tertiary care centres. Participants: Fifty‐seven participants, diagnosed and treated for glaucoma. Methods: Participants received oral placebo or nicotinamide and reviewed six‐weekly. Participants commenced 6 weeks of 1.5 g/day then 6 weeks of 3.0 g/day followed by crossover without washout. Visual function measured using electroretinography and perimetry. Main outcome measures: Change in inner retinal function, determined by photopic negative response (PhNR) parameters: saturated PhNR amplitude (Vmax), ratio of PhNR/b‐wave amplitude (Vmax ratio). Results: PhNR Vmax improved beyond 95% coefficient of repeatability in 23% of participants following nicotinamide vs 9% on placebo. Overall, Vmax improved by 14.8% [95% CI: 2.8%, 26.9%], ( P = .02) on nicotinamide and 5.2% [−4.2%, 14.6%], ( P = .27) on placebo. Vmax ratio improved by 12.6% [5.0%, 20.2%], ( P = .002) following nicotinamide, 3.6% [−3.4%, 10.5%], ( P = .30) on placebo. A trend for improved visual field mean deviation was observed with 27% improving ≥1 dB on nicotinamide and fewer deteriorating (4%) compared to placebo ( P = .02). Conclusions: Nicotinamide supplementation can improve inner retinal function in glaucoma. Further studies underway to elucidate the effects of long‐term nicotinamide supplementation.